Only mothers feed mature offspring in European Ceratina bees - Mikát, Michael; Waldhauserová, Jitka; Fraňková, Tereza; Čermáková, Kateřina; Brož, Vojtěch; Zeman, Šimon; Dokulilová, Marcela; Straka, Jakub (Insect science, 2021)
Parental care directed to adult offspring is uncommon in animals. Such parental care has been documented in Xylocopinae bees (Hymenoptera: Apidae). Moreover, some Ceratina bees (Xylocopinae) are known to feed mature siblings, and feeding of mature siblings is achieved by dwarf eldest daughters when mothers died. These daughters are intentionally malnourished by mothers and usually originate from the first brood cell. Here, we examined the pattern of care provided to young adults in three small European carpenter bees: Ceratina (Ceratina) cucurbitina, C. (Euceratina) chalybea, and C. (E.) nigrolabiata. Observations of nest departures and arrivals were performed to study foraging behavior. We detected intensive foraging behavior of mothers in all three studied species. However, we did not observe regular foraging behavior of daughters in any species. The experimental removal of mothers in C. cucurbitina led to the emigration of young adults and did not initiate foraging activity in daughters. We conclude that the feeding of siblings does not occur in these species unlike in the American species C. calcarata. We detected female-biased sex ratios in the first brood cell in C. cucurbitina and C. chalybea. Female offspring in the first brood cell was smaller than other female offspring only in C. cucurbitina. Our results show that a female-biased sex ratio and the small size of daughters in the first brood cell do not provide sufficient evidence for demonstrating the existence of an altruistic daughter and also that the pattern of maternal investment is not exclusively shaped by social interactions.
Keywords: apetenční chování; Animals; provisioning; sociality; stravovací zvyklosti; včely; Xylocopinae; Female; zvířata; Bees; maternal care; Feeding Behavior; foraging trip; Appetitive Behavior; Hymenoptera; ženské pohlaví